Food quality impacts on reproductive traits, development and fatty acid composition of the freshwater calanoid copepod Eudiaptomus sp. (21st June 2022) - Titocci, Jessica; Fink, Patrick
Abstract: The nutritional quality of phytoplankton is essential for the fitness of herbivorous zooplankton and for efficient carbon fluxes in pelagic ecosystems. In freshwater lakes, cladocerans and calanoid copepods are the main pelagic herbivores in terms of both numbers and grazing impact. However, most studies focused on the easily cultivable cladocerans, while only few studies addressed the impact of the diet on freshwater calanoid copepods due to their more complex life cycle. We here supplied five different phytoplankton diets to the freshwater calanoid copepod Eudiaptomus sp. to investigate their dietary quality for the copepods' fitness traits over the copepod's entire life cycle. While all tested diets supported comparable reproductive success in adults, egg production, hatching success and survival rate differed markedly between diets. In the offspring generation, diet affected developmental and reproductive periods, size at first reproduction and clutch size. Eudiaptomus body fatty acid composition only partially reflected their diet, indicating that the copepods are able to selectively accumulate and interconvert certain essential fatty acids. This capability may allow them to cope with nutritional deficiencies and may thus be interpreted as an ecological adaptation strategy to the fluctuating environmental conditions and resource availabilities in freshwater plankton.